Engagement and Preparedness of Urban Accredited Social Health Activists (U-ASHAs) for Delivery of Tuberculosis (TB) Care: Findings From two Cities in Maharashtra, India - Vidula S. Purohit; Shilpa Santosh Karvande; Daksha Y. Shah; Omprakash B. Vallepawar; Omprakash J. Yadav; Nerges F. Mistry (Indian Journal of Community Medicine)
Finding missing tuberculosis (TB) cases from the “under-reached” population of urban slums and connecting them with TB services is a priority and ongoing challenge for India. It requires the effective engagement of community health workers including urban Accredited Social Health Activists (U-ASHAs). The study aimed to understand the current engagement of U-ASHAs in TB care and their commensurate preparedness in terms of TB knowledge and training. An exploratory study was conducted in Mumbai and Pune cities of Maharashtra during 2022–23. The study used a mixed-methods approach, including a semi-structured survey of U-ASHAs (n = 222) and in-depth interviews with relevant stakeholders (n = 33). The statistical analysis used was descriptive statistics using MS Excel. The average age and work experience of U-ASHAs were 35.4 (21–50) years and 2.7 (0.5–6) years, respectively. They considered maternal child health services as their main portfolio and TB as an ancillary program. They were mainly involved in a biannual active case finding (ACF) and were recently envisioned as TB treatment supporters with poor clarity about other roles in TB care. Just half-day training for TB as part of 8-day general induction training, brief updates before ACFs, and the absence of an on-the-job supervisory structure resulted in TB knowledge gaps particularly for the latest diagnostic tests, adverse drug reactions, government schemes for TB patients, and contact tracing. Conclusions: Intermittent TB activities coupled with insufficient training impede U-ASHAs’ functionality in TB care. Clarity of TB-related roles, integration of TB activities in daily tasks, comprehensive training, and on-the-job supervisory structures have merit in strengthening U-ASHAs’ engagement in urban TB care.